Coherent Noise Suppression of Single-Shot Digital Holographic Phase Via an Untrained Self-Supervised Network - Tang, Ju; Zhang, Jiawei; Wu, Ji; Di, Jianglei; Zhao, Jianlin (Frontiers in Photonics, 2022)
In digital holography, the coherent noise affects the measurement accuracy and reliability greatly due to the high spatial and temporal coherence of laser. Especially, compared with the speckle noise of intensity in digital holography, the coherent noise of phase contains more medium and low frequency characteristics, which hinders the effectiveness of noise suppression algorithms. Here we propose a single-shot untrained self-supervised network (SUSNet) for the coherent noise suppression of phase, requiring only one noisy phase map to complete the optimization and learning. The SUSNet can smooth and suppress the background fluctuations, parasitic fringes, and diffraction loops in noisy phase, and shows good generalization performance for samples with different shapes, sizes, and phase ranges. Compared with the traditional algorithms and the ground truth-supervised neural network (DnCNN), the SUSNet has the best noise suppression performance and background smoothing effect. As a result, the SUSNet can suppress the fluctuation range to ~20% of the original range.